Utilization Of Antenatal Care Services in A Rural Field Practice Area in Coastal Part of South India - Darshan Bhagwan; Ashwini Kumar; Chythra R Rao; Asha Kamath (Medsci Publications, 2016)
Introduction: Utilization of services during pregnancy will lead to further utilization of additional maternal services. The utilization of these services is not universal which was reflected during National Family Health Survey 3. Objective: To evaluate the utilization of antenatal care services among mothers in south India. Methods: The present community based cross sectional study was conducted among rural mothers who had delivered one year back and accompanied their children for immunization at the rural health centres. A semi-structured Proforma was used and detailed information regarding sociodemographic details and utilization of antenatal services was collected. Results: The study included a total of 300 antenatal mothers. Majority of the antenatal mothers had their antenatal checkups in private set-ups (n=257, 85.7%) and had their first antenatal check up in the first trimester (n=262, 85.3%).Around 95% of the study subjects had consumed more than 100 Iron and Folic Acid tablets. Conclusion: Utilization of antenatal care is much higher in the present study as compared to other available literature for the entire country. Consistent and focused efforts are needed to sustain and consolidate the good coverage and utilization of antenatal services.